2004
DOI: 10.1046/j.1460-9592.2003.01173.x
|View full text |Cite
|
Sign up to set email alerts
|

The laryngeal mask airway for administration of surfactant in two neonates with respiratory distress syndrome

Abstract: We report the successful use of the Classic laryngeal mask airway to provide brief access to the intratracheal space for the administration of surfactant in two neonates with respiratory distress syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 7 publications
(10 reference statements)
0
40
0
Order By: Relevance
“…(7) A year later, in Italy, eight newborns with RDS between 28 and 35 weeks were satisfactorily treated with surfactant using the classic LMA number 1. The procedure was well tolerated, with no need for sedatives or analgesics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(7) A year later, in Italy, eight newborns with RDS between 28 and 35 weeks were satisfactorily treated with surfactant using the classic LMA number 1. The procedure was well tolerated, with no need for sedatives or analgesics.…”
Section: Discussionmentioning
confidence: 99%
“…The use of nebulized surfactant still faces technical difficulties that prevent a final demonstration of its efficacy in vivo. In recent years, studies have been published describing the nasopharyngeal instillation of surfactant in the delivery room, (5) administration via a thin endotracheal catheter (6,7) or via a laryngeal mask airway (LMA). (2) The initial results in a small number of patients suggested LMA as a possible alternative route for surfactant treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Case reports by Brimacombe et al [33], Trevisanuto et al [34], and Micaglio et al [35] demonstrate the feasibility of LMA for surfactant administration. A recent study reported a significant reduction of FiO 2 (at baseline: 0.41 ± 0.04 and after 3 h: 0.23 ± 0.01) in 4 neonates after surfactant administration by using an Air-Q self-pressurizing LMA (size 0.5).…”
Section: Surfactant Administrationmentioning
confidence: 95%
“…In 2004, surfactant administration using a LMA was first described in a case report by Brimacombe et al [54]. A pilot randomized controlled trial in 26 preterm infants with birth weight >1,200 g compared surfactant given by LMA to CPAP and found a marked decrease in oxygen requirement in infants who received surfactant via LMA [55].…”
Section: New Techniques Of Surfactant Administrationmentioning
confidence: 99%